Family Christmas at the Watkins' Home - Watkins, Howard::::::::: (1980)
George Kamp, Christine Watkins, Frances Kamp, Adam Watkins, Albert Watkins; back: Patricia Kamp, Rose Watkins, Jerry Kamp, Howard Watkins